2004
DOI: 10.1021/ma030297w
|View full text |Cite
|
Sign up to set email alerts
|

Polyacrylamide Adsorption from Aqueous Solutions on Gold and Silver Surfaces Monitored by the Quartz Crystal Microbalance

Abstract: Viscoelastic properties of ultrathin films are important in such applications as polymer-supported lipid bilayers, and the quartz crystal microbalance (QCM) offers the ability to measure these properties in situ. In this study, polymer films are created by adsorbing polyacrylamide to gold and silver surfaces from aqueous solutions. The molecular weight of the polymers ranges from 10 000 to 1 000 000 g/mol, and concentrations range from dilute to the overlap concentration. Using a continuum mechanics viscoelast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
85
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(90 citation statements)
references
References 65 publications
5
85
0
Order By: Relevance
“…To calculate the true sensed mass, taking into account any effect of the viscoelastic properties of the adsorbed layer, the equivalent mass was calculated using equation (4) for the different harmonics. The frequency shifts obtained after correcting for bulk effects as described above were used as df in equation (4).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To calculate the true sensed mass, taking into account any effect of the viscoelastic properties of the adsorbed layer, the equivalent mass was calculated using equation (4) for the different harmonics. The frequency shifts obtained after correcting for bulk effects as described above were used as df in equation (4).…”
Section: Resultsmentioning
confidence: 99%
“…The frequency shifts obtained after correcting for bulk effects as described above were used as df in equation (4). The true sensed mass obtained is shown as triangles in figures 2-4.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this experiment F1 and D1 were ignored as they were not reliable. 20,21 Frequency and dissipation values were recorded in air for all crystals. All liquids were allowed to reach room temperature before introduction into the QCM-D chamber, which was set to 25°C.…”
Section: Quartz Crystal Microbalancementioning
confidence: 99%
“…QCM applications have been extended to measure viscoelastic macromolecular interactions with the surfaces of fluids including natural and synthetic macromolecules such as DNA [5,6], proteins [7,8], microorganisms [9], endothelial cells [10], polymers [11][12][13], and polyelectrolyte multilayers [14]. Through these studies, QCM measurements have shown that viscoelastic fluids containing macromolecules exhibit different behavior from that of Newtonian fluids.…”
Section: Introductionmentioning
confidence: 99%